Inclusive school leadership in challenging urban communities - Michalak, Joanna M. (Šolsko polje, 2012)
The aim of the paper is to explore what is perceived to be successful school leadership in the challenging urban communities in Poland and England. This paper reports on outcomes from two case studies. These studies were conducted in two groups of schools in challenging urban communities in Lodz, Poland and in the Yewlands area of Sheffield, England. This paper builds upon outcomes so far from a three-year joint project (2008 - 2011) and firstly presents some differences of context and approach towards school leadership in the Polish and English studies. However, significant similarities in terms of pedagogy and leadership between the two contexts constitute what can be characterised as inclusive school leadership in three main areas: teacher leadership, building "social capital" and in the adoption of subversive approaches.
Keywords: leadership; ravnatelji; vodenje; disadvantaged areas; education; vzgoja in izobraževanje; študije primerov; case studies; comparative research; primerjalne raziskave; Poland; Poljska; Anglija; England